2021
DOI: 10.3390/antiox11010020
|View full text |Cite
|
Sign up to set email alerts
|

Lemongrass Essential Oil Components with Antimicrobial and Anticancer Activities

Abstract: The prominent cultivation of lemongrass (Cymbopogon spp.) relies on the pharmacological incentives of its essential oil. Lemongrass essential oil (LEO) carries a significant amount of numerous bioactive compounds, such as citral (mixture of geranial and neral), isoneral, isogeranial, geraniol, geranyl acetate, citronellal, citronellol, germacrene-D, and elemol, in addition to other bioactive compounds. These components confer various pharmacological actions to LEO, including antifungal, antibacterial, antivira… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 163 publications
(215 reference statements)
0
53
0
Order By: Relevance
“…Nevertheless, the damaging effects of salinity can vary depending on its concentration and plant adaptability ( Munns and Tester, 2008 ). Considering a growing market for lemongrass and its essential oil ( Haque et al, 2018 ; Mukarram et al, 2021a , b ), the present experiment traces the salt-sensitivity of lemongrass and the efficacy of its defence system against salinity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the damaging effects of salinity can vary depending on its concentration and plant adaptability ( Munns and Tester, 2008 ). Considering a growing market for lemongrass and its essential oil ( Haque et al, 2018 ; Mukarram et al, 2021a , b ), the present experiment traces the salt-sensitivity of lemongrass and the efficacy of its defence system against salinity.…”
Section: Discussionmentioning
confidence: 99%
“…The lemongrass essential oil (LEO) has enormous medicinal and commercial potential. The pharmacological benefits of LEO are derived from its antimicrobial, anticancer, insect-repellent, and antioxidant properties ( Mukarram et al, 2021a , b ). These bioactivities are further exploited in cosmetics and food packaging and safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological effects of geraniol suggest that it could be a viable medication candidate for treating a variety of diseases thanks to its anti‐cancer, anti‐inflammatory, antioxidative, antibacterial, hepatoprotective, cardioprotective, and neuroprotective properties [17–19] . Especially, the monoterpenes geraniol and geranyl acetate, volatile bioactive compounds, present in the Distichochlamys citrea and several other plants were proved to exhibit significant anticancer activities against colon cancer cells [20] . In these reports, evidences indicated that they are promising for the development of new cancer therapies, thus deserving further investigations.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] Especially, the monoterpenes geraniol and geranyl acetate, volatile bioactive compounds, present in the Distichochlamys citrea and several other plants were proved to exhibit significant anticancer activities against colon cancer cells. [20] In these reports, evidences indicated that they are promising for the development of new cancer therapies, thus deserving further investigations. In many preceding studies, ethyl linoleate, a naturally occurring fatty acid ester, was consistently reported with wide bioactive potential, e. g. anti-inflammatory, [21,22] antibacterial, [23] antiacne, [24] and melanogenesis-inhibitory properties.…”
Section: Chemistryselectmentioning
confidence: 99%